The role of Anti-PAD4, Anti-CarP, and Anti-RA33 antibodies combined with RF and ACPA in predicting abatacept response in rheumatoid arthritis - Alberto Floris; Maria Maddalena Angioni; Mattia Fadda; Micaela Rita Naitza; Mattia Congia; Elisabetta Chessa; Matteo Piga; Alberto Cauli (Arthritis Research & Therapy)
Abstract Objectives To explore the role of newly emerging autoantibodies (AAbs) - peptidyl-arginine deiminase 4 (aPAD4), carbamylated proteins (aCarP), and anti-RA33 (aRA33) - alongside the traditionally assessed rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA), in predicting the response to abatacept (ABT) and its retention rate in rheumatoid arthritis (RA) patients. Methods Data from 121 consecutive ABT-treated RA patients were recorded. The RF and ACPA status were retrospectively assessed by reviewing the patients’ clinical records. Positivity for aPAD4, aCarP and aRA33 were determined by Enzyme-Linked Immunosorbent Assay (ELISA). The achievement of a moderate or good EULAR response at 6 months and the 3-years retention were analyzed as treatment outcomes. Multiple logistic regression models and Cox regression hazard analysis models were built to identify the association between such outcomes and the different AAbs, after adjustment for different confounders. The AAbs were assessed both individually and in different combinations to identify the most robust predictive model. Results In the studied cohort, RF, ACPA, aPAD4, aCarP and aRA33-Ab tested positive in 74.4%, 69.4%, 43.8%, 23.9%, 14.9% patients, respectively. A moderate or good EULAR response at 6 months was achieved by 64.5% of subjects and the cumulative 3-years retention rate was 56.6%. A higher EULAR response rate was recorded in patient with positivity for RF (67% in subjects tested positive vs. 58% in negative), ACPA (68% vs. 57%), aPAD4 (68% vs. 62%), and aCarP (72% vs. 62%), although statistical significance was not reached likely due to sample size limitations. Similarly, ACPA, aPAD4, aCarP were associated with higher 3-year retention rates, though not statistically significant individually. The combined analysis revealed that positivity for ACPA and/or aPAD4 predicted a significantly higher EULAR response rate at 6 months compared with double negativity (adjusted OR 2.7, p 0.026). Furthermore, positivity for at least one of ACPA, aPAD4, or aCarP predicted a significantly higher 3-year ABT retention rate compared to triple negativity (62.1% single or double positive vs. 33.5% triple negative, adjusted HR 0.48, p 0.022). Conclusion This study highlights the potential benefits of using a combined assessment of ACPA aPAD4 and aCarP in predicting effectiveness of ABT in RA.